2021
DOI: 10.1590/1806-9665-rbent-2020-0078
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the antennal sensilla of two species of Hoplopyga Thomson, 1880 (Coleoptera, Scarabaeidae, Cetoniinae)

Abstract: Antennal sensilla are important functional elements of sensory systems in insects. This study aimed to determine the morphology and structure of the sensilla of two species of the genus Hoplopyga. Adults of Hoplopyga liturata (Olivier, 1789) were collected in traps with sugarcane juice as an attractant. Thereafter, larvae of Hoplopyga albiventris (Gory and Percheron, 1833) were collected in mounds of termites (Cornitermes cumulans (Kollar, 1832) Isoptera). Then, they were reared in the laboratory for adult obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…4A) and restricted the term sensilla basiconica to longer sensilla surrounded or not by a pit. The sensilla basiconica found on genera Cyclocephala (Dynastinae: Cyclocephalini; Saldanha et al, 2020;Nagamine et al, 2022) and Anomala (Rutelinae: Anomalini; Rodrigues et al, 2019) are not found in Cetoniinae genera of the tribe Gymnetini: Cotinis (described by Baker and Monroe, 2005), Gymnetis (by present study), and Hoplopyga (by Costa et al, 2021); and are also not found in other flower chafers as Osmoderma (Osmodermatini; by Zauli et al, 2016: sensilla basiconica sub-type 1 is here interpreted as a sensilla coeloconica variation) and Pachnoda (by Bengtsson et al, 2011).…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations
“…4A) and restricted the term sensilla basiconica to longer sensilla surrounded or not by a pit. The sensilla basiconica found on genera Cyclocephala (Dynastinae: Cyclocephalini; Saldanha et al, 2020;Nagamine et al, 2022) and Anomala (Rutelinae: Anomalini; Rodrigues et al, 2019) are not found in Cetoniinae genera of the tribe Gymnetini: Cotinis (described by Baker and Monroe, 2005), Gymnetis (by present study), and Hoplopyga (by Costa et al, 2021); and are also not found in other flower chafers as Osmoderma (Osmodermatini; by Zauli et al, 2016: sensilla basiconica sub-type 1 is here interpreted as a sensilla coeloconica variation) and Pachnoda (by Bengtsson et al, 2011).…”
Section: Discussionmentioning
confidence: 46%
“…With the development of the present study, the studies with the antennal sensilla of Cetoniinae were expanded to 20 species (Meinecke, 1975;Baker and Monroe, 2005;Zauli et al, 2016;Bohacz et al, 2020;Costa et al, 2021; present study): Cetonia aurata (Linnaeus, 1758), Cotinis nitida (Linnaeus, 1758), Epicometis hirta (Poda 1761), Gnorimus nobilis (Linnaeus, 1758), Gymnetis holosericea, Gymnetis rufilateris, Hoplopyga albiventris (Gory and Percheron, 1833), Hoplopyga liturata (Olivier, 1789), Leucocelis elegans, Mausoleopsis amabilis, Osmoderma eremita (Scopoli, 1763), Oxythyrea funesta (Poda 1761), Pachnoda ephippiata (Gerstaecker, 1867), Pachnoda marginata (Drury, 1773), Pachnoda interrupta (Olivier, 1789), Potosia affinis (Andersch, 1797), Potosia cuprea (Fabricius 1775), Protaetia morio (Fabricius, 1781), Trichius fasciatus (Linnaeus, 1758), and Valgus hemipterus (Linnaeus, 1758). Otherwise, the quantification of sensilla of males and females are known to (Costa et al, 2021; present study): Hoplopyga albiventris, Hoplopyga liturata, Gymnetis holosericea, and Gymnetis rufilateris.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An undetermined species of Cyclocephala studied by Bohacz et al (2020) was described with a "brush-like sensilla trichodea". Hair-like sensilla grouped in a brush-like structure (or "field of setae") occur in Dynastinae (Bohacz et al 2020) and at least in some Cetoniinae (Bohacz et al (2020) to Valgus hemipterus (Linnaeus, 1758); Costa et al (2021) to two species of Hoplopyga).…”
Section: Discussionmentioning
confidence: 99%